Genetic Diversity of Sangihe Nutmeg (Myristica fragrans Houtt.) Based on Morphological and ISSR Markers - Tanti Agustina; Abdul Razaq Chasani; Budi Setiadi Daryono; Muhammad Said Rifqi (Scientifica)
Sangihe nutmeg is an important crop because of its usefulness in the pharmacology, spices and cosmetics industries. Sangihe is the oldest active subduction zone island in the Indonesia–Philippines region, where frequent tectonic earthquakes and the geographic and reproductive isolation of Sangihe nutmeg occur. This isolation results in adaptation and speciation because of increasing variability. Using morphological and molecular approaches, we aimed to assess the genetic variety of Sangihe nutmeg based on morphological and intersimple sequence repeat (ISSR) markers. In total, 31 morphological characteristics were examined, and molecular data of ISSR markers using five primers were analysed based on numerical taxonomy using the unweighted pair group method with arithmetic mean (UPGMA) and principal component analysis (PCA) methods. Results showed five major groups of Sangihe nutmeg based on seed variation, that is, thick round, thin round, thick oval, thin oval, and twin seeds, whereas the presence of variation in molecular characters was indicated by DNA polymorphisms between 0% and 33.33%. The phenetic relationships within Sangihe nutmeg, based on morphological and ISSR markers, exhibit two groups with different member compositions. The major morphological characteristics influencing the phenetic relationship pattern were tree shape, leaf shape, fruit shape, number of fractions when ripe, fruit size index, number of fruit indentations, indentation, aryl density, seed shell, and number of seeds.